Pendampingan Pelatihan Peningkatan Kualitas Program OSIS (Organisasi Siswa Intra Sekolah) dalam Karya Tulis Ilmiah di SMP Islam Nahdlatul Ulama Galis Bangkalan - munib; Siti Farida; Badtuttamam; Nur Jamal; Zainuddin (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Nahdlatul Ulama Galis Bangkalan Islamic Junior High School is one of the schools that always has significant changes in the use of social media. Without realizing it, the use of social media can affect the learning received by students. This mentoring aims to investigate the influence of social media on the learning level of students of Nahdlatul Ulama Galis Bangkalan Islamic Junior High School. Mentoring Training to Improve the Quality of the OSIS Program (Intra-School Student Organization) in Scientific Writing to students of Nahdlatul Ulama Galis Bangkalan Islamic Junior High School who are still in the learning process. In this activity, we will focus on OSIS activities. The mentors in this activity are in an effort to provide mentoring in the form of Training to Improve the Quality of the OSIS Program (Intra-School Student Organization) in Scientific Writing to students of Nahdlatul Ulama Galis Bangkalan Islamic Junior High School. This condition indicates that the higher the intensity of writing, the higher the level of student learning. The implication of this mentoring program is the importance of providing motivation and guidance in writing among students at Nahdlatul Ulama Galis Islamic Middle School in Bangkalan to improve the quality of their education